(±)-Gossypol induces apoptosis and autophagy in head and neck carcinoma cell lines and inhibits the growth of transplanted salivary gland cancer cells in BALB/c mice. (3rd April 2017) - Benvenuto, Monica; Mattera, Rosanna; Masuelli, Laura; Taffera, Gloria; Andracchio, Orlando; Tresoldi, Ilaria; Lido, Paolo; Giganti, Maria Gabriella; Godos, Justyna; Modesti, Andrea; Bei, Roberto
Abstract: Racemic Gossypol [(±)-GOS], composed of both (−)-GOS and (+)-GOS, is a small BH3-mimetic polyphenol derived from cotton seeds. (±)-GOS has been employed and well tolerated by cancer patients. Head and neck carcinoma (HNC) represents one of the most fatal cancers worldwide, and a significant proportion of HNC expresses high levels of antiapoptotic Bcl-2 proteins. In this study, we demonstrate that (±)-GOS inhibits cell proliferation and induces apoptosis and autophagy of human pharynx, tongue, and salivary gland cancer cell lines and of mouse salivary gland cancer cells (SALTO). (±)-GOS was able to: (a) decrease the ErbB2 protein expression; (b) inhibit the phosphorylation of ERK1/2 and AKT; (c) stimulate p38 and JNK1/2 protein phosphorylation. (±)-GOS administration was safe in BALB/ c mice and it reduced the growth of transplanted SALTO cells in vivo and prolonged mice median survival. Our results suggest the potential role of (±)-GOS as an antitumor agent in HNC patients.